THE ROLE OF VISUAL DESIGN FRAMEWORKS FOR PHOTOGRAPHY-ART RELATIONS - Ozkececi, Ilhan; Cicek, Erkan (ISTANBUL UNIV, RESEARCH INST TURKOLOGY, DEPT ART HISTORY, 2017)
Photography as interdisciplinary art is important. The art of photography is the document of art. In this study, the role of visual design elements in the art-related relation is mentioned. Located in Plastic Items; Items such as Line, Tone, Color, Shape and Unity were evaluated in conjunction with visual and descriptive examples. This article has been examined in the framework of Visual Design Elements, centered on photographs. In the introduction section; Texts, definitions, objectives, scope and method are explained. In the next section, photographic examples are given for Visual Design Elements. In the conclusion section, visual design elements are evaluated and discussed on photographic examples.
Keywords: art; photography; media; communication; visual design